Peran Guru dan Teman Sebaya dalam Kelancaran Pembelajaran bagi Siswa Tunarungu di SMK Marsudirini Surakarta - Selvi Nurlita Anggraini (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Inclusive education is an approach that emphasizes equality and diversity in the learning process, including providing equal learning opportunities for students with special needs. This study aims to see the role of teachers and peers in supporting the smooth learning of students. This study uses a qualitative descriptive method with data collection techniques through observation and interviews. The results of the study indicate that the role of teachers is very important in creating effective learning according to the needs of all students, students use instant transcription applications to follow the learning. On the other hand, the role of friends also plays a very important role in building an inclusive environment through communication with sign language and positive social interactions, with the determination of those who are trying to learn sign language. Collaboration between teachers and peers can provide emotional and academic support that encourages all students to excel. This study emphasizes the importance of collaboration between all parties in order to realize effective and equitable inclusive education.